Electrical and viscoelastic parameters of erythrocytes as predictors of exacerbation in inflammatory bowel diseases - M. V. Kruchinina; I. O. Svetlova; A. V. Azgaldyan; A. A. Gromov; V. M. Generalov; I. N. Yakovina; A. A. Shestov (Сибирский научный медицинский журнал, 2021)
The aim of this work is to study the electrical and viscoelastic parameters of erythrocytes for patients with inflammatory bowel diseases (IBD), examined in dynamics, as possible predictors of exacerbation of the disease. Material and methods. In dynamics, 23 patients with IBD (37.9 ± 4.3 years) were examined. The first examination was carried out in the stage of exacerbation, the second – after 6–12 months – in the stage of remission of IBD. Additionally, 36 patients with IBD in remission were examined to assess the predictive capabilities of erythrocyte parameters with subsequent monitoring of their condition for 6–12 months. The electrical and viscoelastic parameters of erythrocytes were investigated by dielectrophoresis. Statistical processing was carried out using a system of machine learning methods – Random Forest, MATLAB (R2019a, MathWorks). Results and discussion. The parameters of erythrocytes, which are predictors of exacerbation of IBD, were revealed: an increase in the proportion of deformed cells (p = 0.0001); altered nature of the erythrocyte surface (p = 0.011); increased electrical conductivity of membranes (p = 0.0019); reduced dipole moment (p = 0.0015), the rate of directional movement of erythrocytes to the electrodes (p = 0.005) (paired and unpaired Volcano plot methods), reduced deformation amplitude at a frequency of 5×105 Hz (p = 0.009), capacity of erythrocyte membranes (p = 0.029 ) (unpaired Volcano plot method). Indicators associated with changes in the charge of cells, the structure of erythrocyte membranes and the level of energy metabolism of the cell turned out to be significant. A high diagnostic accuracy of these indicators was established as predictors: the proportion of deformed cells (AUC 0.939), a summarized viscosity index (AUC 0.932). Cluster analysis of the values of erythrocyte parameters – predictors of exacerbation made it possible to stratify the risk of exacerbation: at the most altered levels of parameters – the development of exacerbation after 2.5–4.5 months, intermediate levels – after 4–6 months, minimally changed – after 8–12 months (predictive accuracy – 92 %). Conclusions. The revealed electrical and viscoelastic parameters of erythrocytes should be considered as promising predictors of exacerbation in patients with IBD.